Three-dimensional motion of particles in a shear flow near a rough wall. (June 2016) - Feuillebois, F.; Gensdarmes, F.; Mana, Z.; Ricciardi, L.; Monier, C.; Le Meur, G.; Reynaud, C.; Rabaud, M.
Abstract: A model is proposed for the three-dimensional motion of a small spherical particle entrained by the shear flow of a gas near a rough wall. On the basis of experimental results, the wall is modeled by an average small roughness and some much larger isolated peaks, which are yet smaller than the sphere radius. When encountering a high peak of roughness, the particle may be lifted if the aerodynamic force and torque take over the force and torque due to adhesion on the wall. The aerodynamics is treated using previous analytical results for the creeping flow around a particle near a wall. Values of the adhesion forces of a particle near a rough wall are obtained experimentally. When lifted from the wall, the particle follows a three-dimensional trajectory while rotating around the peak of roughness. Examples of calculated trajectories show that the particle may or may not reach the top of the peak, depending on the various physical parameters. Since the velocity of the particle when leaving the peak grows with its final distance from the wall, that velocity is essential for the subsequent particle resuspension by the ambient shear flow. Abstract : Highlights: A particle in contact with a peak of asperity may describe various 3D trajectories. Aerodynamics of a particle in a shear flow and wall roughness are considered in the modeling. A realistic particle-wall adhesion force from experiment is introduced in the model. A particle lifted from the rough wall may or may not reach the top of a peak of asperity, depending on the various physical parameters. The position and velocity of a particle leaving the rough wall are provided by the model.